Answer:
-2
Step-by-step explanation:
Hmm idk.... I need like more info for this please so I can help you thank you byeeeee
Let's solve this by substitution.
y is given by the 2nd eqn as y = (1/3)x + 7. Subst. (1/3)x + 7 into the first eqn as a replacement for y: x + 9( (1/3)x + 7) = 3.
clear out fractions by mult. all 3 terms by 3: 3x + 9x + 63 = 3
Combine like terms: 12x = -60. Then x = -5
Find y by subst. -5 for x in the 2nd equation: y = (1/3)(-5) + 7
= -5/3 + 35/3 = 30/3 = 10.
Thus, the solution (x,y) of this system is (-5,10).
Answer:
A
Step-by-step explanation:
-1/2+c=31/4
-1/2+c+1/2=31/4+1/2
c=33/4